Back of beyond - Box, C. J. (New York : Minotaur Books, 2011)
Cody Hoyt, while a brilliant cop, is an alcoholic struggling with two months of sobriety when his mentor and AA sponsor Hank Winters is found burned to death in a remote mountain cabin. At first it looks like the suicide of a man who's fallen off the wagon, but Cody knows Hank better than that. Sober for fourteen years, Hank took pride in his hard-won sobriety and never hesitated to drop whatever he was doing to talk Cody off a ledge. When Cody takes a closer look at the scene of his friend's death, it becomes apparent that foul play is at hand. After years of bad behavior with his department, he's in no position to be investigating a homicide, but this man was a friend and Cody's determined to find his killer.
Keywords: Detectives -- Montana -- Fiction; Recovering alcoholics -- Fiction; Murder -- Investigation -- Fiction; Fathers and sons -- Fiction; Packhorse camping -- Yellowstone National Park -- Fiction; Packhorse camping -- Wyoming -- Fiction; Helena National Forest (Mont.) -- Fiction; Mystery fiction; Suspense fiction